A review of current advancements for wound healing: Biomaterial applications and medical devices - Deng, Xiaoxuan; Gould, Maree; Ali, M. Azam (Journal of biomedical materials research. Part B, Applied biomaterials, 2022)
Wound healing is a complex process that is critical in restoring the skin's barrier function. This process can be interrupted by numerous diseases resulting in chronic wounds that represent a major medical burden. Such wounds fail to follow the stages of healing and are often complicated by a pro‐inflammatory milieu attributed to increased proteinases, hypoxia, and bacterial accumulation. The comprehensive treatment of chronic wounds is still regarded as a significant unmet medical need due to the complex symptoms caused by the metabolic disorder of the wound microenvironment. As a result, several advanced medical devices, such as wound dressings, wearable wound monitors, negative pressure wound therapy devices, and surgical sutures, have been developed to correct the chronic wound environment and achieve skin tissue regeneration. Most medical devices encompass a wide range of products containing natural (e.g., chitosan, keratin, casein, collagen, hyaluronic acid, alginate, and silk fibroin) and synthetic (e.g., polyvinyl alcohol, polyethylene glycol, poly[lactic‐co‐glycolic acid], polycaprolactone, polylactic acid) polymers, as well as bioactive molecules (e.g., chemical drugs, silver, growth factors, stem cells, and plant compounds). This review addresses these medical devices with a focus on biomaterials and applications, aiming to deliver a critical theoretical reference for further research on chronic wound healing.